2014
DOI: 10.1007/s10732-014-9258-x
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic strategies for assessing wireless sensor network resiliency: an event-based formal approach

Abstract: Wireless Sensor Networks (WSNs) are increasingly being adopted in critical applications. In these networks undesired events may undermine the reliability level; thus their effects need to be properly assessed from the early stages of the development process onwards to minimize the chances of unexpected problems during use.In this paper we propose two heuristic strategies: what-if analysis and robustness checking. They allow to drive designers towards optimal WSN deployment solutions, from the point of view of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The authors presented the simulation, assessments, and critical analysis in various categories. Alessandro Testa et al 75 have proposed an approach to analyze the effect of undesired events over reliability constraint. Effect of this type of event must be identified before the development and deployment of applications.…”
Section: Middleware Approaches For Wsnsmentioning
confidence: 99%
“…The authors presented the simulation, assessments, and critical analysis in various categories. Alessandro Testa et al 75 have proposed an approach to analyze the effect of undesired events over reliability constraint. Effect of this type of event must be identified before the development and deployment of applications.…”
Section: Middleware Approaches For Wsnsmentioning
confidence: 99%
“…Heuristics are strategies derived from previous experiences with similar problems. These strategies rely on using readily accessible, though loosely applicable, information to control problem-solving in human beings, machines, and abstract issues (Ippoliti, 2015;Şahin, Duran, Yakıcı, & Şahin, 2018;Testa, Cinque, Coronato, De Pietro, & Augusto, 2015). In BPM, redesign heuristics exist as a method that builds upon an extensive set of redesign options (Reijers & Liman Mansar, 2005).…”
Section: Redesign Heuristicsmentioning
confidence: 99%
“…In [28,29], the authors showed that most of the popular formal approaches are based on theoretical models such as finite state machine, timed automata and process algebra. Finite state machine approaches have been pointed out for the difficulty in dealing with hierarchical models.…”
Section: Related Workmentioning
confidence: 99%